Ancaman Cyberterrorism di Indonesia dan Respons Negara - I Putu Hadi Pradnyana; Muhammad Syaroni Rofii (Neolectura, 2020)
This article intend to elaborate the threats from cyberterrorism in Indonesia and the anticipation or response made by the state. That tactically, terrorist groups have made various changes and adjustments to launch a plan of terror action. When a target is deemed to be highly secure and difficult to penetrate, the terrorist group then carries out a series of tactical evolutions targeting more vulnerable targets. This praxis is shown in the practices of terrorism that have changed during the last hundred years until now it has adapted to a form of cyberterrorism. This research uses qualitative methods and types of phenomenology. The phenomenon of cyberterrorism is linked to the threat in Indonesia and the government's response to anticipating this problem. The research result shows that most of the terrorist groups in the world, including in Indonesia, have used cyber means to attack certain targets. In responding to cyberterrorism crimes, Indonesia has made several efforts to tackle cyberterrorism through the establishment of special agencies and strengthening regulations. However, there are still things that need to be addressed in order to strengthen the national security system from the threat of cyberterrorism.